Peer Counseling as an Alternative to Psychological Support in Schools - Noviya, Noviya (PT. Anagata Sembagi Education, 2025)
Mental health problems among students are increasing, while the number of professionals such as psychologists and counselors is still limited in many schools. Peer counseling has emerged as an effective alternative in providing psychological support in educational settings. This study aims to explore the effectiveness of peer counseling as an alternative psychological service for students in schools. With a qualitative descriptive approach and case studies in several secondary schools in Indonesia, data were collected through in-depth interviews, observations, and documentation. The results of the study indicate that peer counseling helps create a supportive environment, increases students' openness in expressing problems, and strengthens social relationships between students. However, the success of this program is highly dependent on adequate training and support from the school. This article recommends the development of policies and systematic training for peer counselors to improve the effectiveness and sustainability of the program.